The sound of brands - Gerd Nufer (Hochschule Reutlingen, ESB Business School, 2018)
The aim of this research paper is to both examine and conceptualise the concept of audio branding. Audio branding is an important part of the overall brand management concept and corporate identity. Strong brands ease the choice for customers and convey values and a certain quality promise. Branding is of vital importance. It needs to be acknowledged that only 0.004% of all outer stimuli reach the human consciousness. Therefore, audio branding is a way to further strengthen the overall brand awareness. This leads to an emotional connection with a brand. This study strives to determine the characteristics of audio branding and to analyse the corporate audio branding of Audi. The result of this research study is the suggestion of the use of audio branding in a way that fits the overall brand picture. Otherwise, the brand communication is inconsistent, and this could lead to a misunderstanding of the brand values for customers. The analysis of the Audi corporate sound design might be beneficial for practitioners. The overall evaluation of the concept of audio branding contributes to the existing body of literature in branding.
urn:nbn:de:bsz:21-dspace-852645
Keywords: 650